2019
DOI: 10.1038/s41467-019-11955-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of off-target toxicity in CRISPR-Cas9 screens for essential non-coding elements

Abstract: Pooled CRISPR-Cas9 screens are a powerful method for functionally characterizing regulatory elements in the non-coding genome, but off-target effects in these experiments have not been systematically evaluated. Here, we investigate Cas9, dCas9, and CRISPRi/a off-target activity in screens for essential regulatory elements. The sgRNAs with the largest effects in genome-scale screens for essential CTCF loop anchors in K562 cells were not single guide RNAs (sgRNAs) that disrupted gene expression near the on-targe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 87 publications
(125 reference statements)
5
127
0
Order By: Relevance
“…This score ranges from 0-1 for targeting guides (with 1 denoting the most specific gRNAs) and takes into account the number, position, and type of mismatch between guide and genomic sequence 11 (Figure 1d, Supplementary Figure 1b). Binning gRNAs targeting non-essential genes based on this score showed that decreasing specificity led to increasing depletion of gRNAs (Figure 1c, right; Supplementary Figure 1c), analogous to what has been recently reported for gRNAs targeting regulatory elements 19 . Importantly, distributions of gRNAs with scores above 0.16 became indistinguishable from those of highly specific guides (specificity = 1; Kolmogorov–Smirnov test, adjusted for multiple testing), suggesting that above this specificity threshold off-targeting no longer interferes with gRNA representation in the library.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This score ranges from 0-1 for targeting guides (with 1 denoting the most specific gRNAs) and takes into account the number, position, and type of mismatch between guide and genomic sequence 11 (Figure 1d, Supplementary Figure 1b). Binning gRNAs targeting non-essential genes based on this score showed that decreasing specificity led to increasing depletion of gRNAs (Figure 1c, right; Supplementary Figure 1c), analogous to what has been recently reported for gRNAs targeting regulatory elements 19 . Importantly, distributions of gRNAs with scores above 0.16 became indistinguishable from those of highly specific guides (specificity = 1; Kolmogorov–Smirnov test, adjusted for multiple testing), suggesting that above this specificity threshold off-targeting no longer interferes with gRNA representation in the library.…”
Section: Resultssupporting
confidence: 81%
“…Second, there is an increasing interest in using CRISPR to identify essential noncoding regulatory sequences in large scale. While GuideScan scores also predict gene-independent depletion of gRNAs in this setting 19 , many of these elements—such as transcription factor binding sites or RNA Binding Protein motifs—are so small in size that only a limited number of gRNAs that can potentially disrupt them, making further filtering unachievable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-nucleotide polymorphisms (SNPs) can be defined as single-nucleotide differences from reference genomes. The targeting efficiency of Cas9 has been examined using data from genome-wide studies combined with machine learning (C HUAI et al 2018; D OENCH et al 2014; L ISTGARTEN et al 2018; N AJM et al 2018; T YCKO et al 2019). The position of specific nucleotides in the target sequences has been shown to affect targeting efficiency, which is the major determinant of CRISPR-Cas9 dependent genetic modification (D OENCH et al 2014; H OUSDEN et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) can be defined as singlenucleotide differences from reference genomes. The targeting efficiency of Cas9 has been examined using data from genome-wide studies combined with machine learning (Chuai et al 2018;Doench et al 2014;Listgarten et al 2018;Najm et al 2018;Tycko et al 2019). The position of specific nucleotides in the target sequences has been shown to affect targeting efficiency, which is the major determinant of CRISPR-Cas9 dependent genetic modification (Doench et al 2014;Housden et al 2015).…”
mentioning
confidence: 99%